Microenvironmental regulation of T-cells in pulmonary hypertension - Plecitá-Hlavatá, Lydie; Brázdová, Andrea; Křivonosková, Monika; Hu, Cheng-Jun; Phang, Tzu; Tauber, Jan; Li, Min; Zhang, Hui; Hoetzenecker, Konrad; Crnkovic, Slaven; Kwapiszewska, Grazyna; Stenmark, Kurt R. (Frontiers in Immunology, 2023)
CM-hPH Fibs -conditioned media from human CO Fibs 24-hour cultivation CO (h)Fibs -fibroblasts from calf (human) pulmonary arteries of healthy animals DCs -dendritic cells dPAscalf distal pulmonary arteries ECAR -extracellular acidification rate PH -pulmonary hypertension IPAHidiopathic pulmonary artery hypertension LPSlipopolysaccharide NK -natural killers PASMC -pulmonary artery smooth muscle cells PAEC -pulmonary artery endothelial cells PH (h)Fibs -fibroblasts from calf (human) pulmonary arteries of animals with pulmonary arterial hypertension ROS -reactive oxygen species TLR4 -toll-like receptor 4